A condição processual e a plasticidade/materialidade nos procedimentos da modelagem e da moldagem, ou, sobre o que não é preciso - Maria Elisa Mendes Miranda (2015)
This work is built through reflections on the process conditions associated with the procedures of modeling and molding. Touch and temporality are proposed as drivers of these processes, in which plasticity and materiality are identified with the force of changes, given the vibrant nature of their corporeality. Contact, the instance that promotes the relationship between form and counter form, establishes the emergence of transformation, the Gordian knot of this research. In order to think about this vital power theorists, such as Didi-Huberman and Rosalind Krauss, among others, are summoned, to join the voices and work of artists, in order to produce a conceptual and imagetic body related to the plastic experience developed in the course of modeling and molding.